Pengaruh Store Atmosphere Terhadap Keputusan Pembelian Di Gramedia Manado - Tansala, Desilsan; Tumbel, Tinneke M.; Walangitan, Olivia F. C. (JURNAL ADMINISTRASI BISNIS, 2019)
Store atmosphere is an atmosphere that refers to the physical characteristics of exterior buildings and interior spaces, which shape the store image and bring in customers. This study aims to determine the effect of store atmosphere on consumer purchasing decisions at Gramedia Manado Sam Ratulangi. The problem in this study is the problem of parking where when going to Gramedia is less comfortable, jammed and narrow, there is a lack of sanitary hygiene, and sometimes changes in shelves and location marks make consumers confused. The type of research used in this study is descriptive quantitative research, using questionnaires and using a Likert scale. The population is all Gramedia Sam Ratulangi Manado consumers whose population size is unknown. Samples taken amounted to 80 respondents using probability sampling method that is by simple random sampling technique. The statistical analysis used in this study is a simple regression analysis using SPSS 25 for windows. The results of this study indicate that store atmosphere has a positive and significant effect on purchasing decisions. The amount of store atmosphere influence on purchasing decisions is 54.7% and 45.3% is influenced by other factors not examined in this study such as product quality, price, promotion and store associate factors that were not examined in this study.